CARAvELA – Competency in Anaesthesiology – self-Reported Assessment on European Learning Aims: a national survey - Carmen Oliveira; Marta Dias Vaz; Luís Gonçalves; Henrique Gouveia; Andrea Tomassi; Andrea Falegnami; Alessandro Caforio; Alessandro Scudellari; Fátima Lima; Federico Bilotta (Medical Education Online)
Introduction Competency-based teaching is the preferred approach for anaesthesia training, however, limited data exists on Portuguese residents’ exposure to essential competencies. This study aimed to evaluate their daily exposure to seven selected competencies from the 2022 European Training Requirements (ETR).Methods A cross-sectional survey was conducted amongst 350 Portuguese anaesthesia residents, throughout a 10 working day period, using a questionnaire with 170 questions. Participants were on either anaesthesia or intensive care unit rotation. Demographic data and scores of exposures to selected competencies were gathered. Statistical analyses included descriptive statistics, comparison of means and a Linear Mixed Model using the restricted maximum likelihood estimation method. The significance threshold was set at p < 0.05.Results Regarding ETR competency exposure, no statistical differences were found based on gender. Residents reported statistically significant higher levels of exposure to competencies while in anaesthesia rotations, except for lung, cardiac and Point-of Care ultrasound. Apart from ultrasound and academic research activities, the maximum exposure level was attained only during anaesthesia rotations. There was no reported exposure to airway ultrasound in any rotation. Exposure to academic research activities, in a scale from 0 to 5, was on average below one. The average reported values for direct patient communication were the highest. As expected, the fifth-year residents reported overall higher scores. Residents from the North reported lower scores for general anaesthesia maintenance, peripheral regional anaesthesia, airway intubation and ventilation management, but higher scores of exposures to academic research activities.Discussion Adopting a national logbook, formative regular assessment, supporting the trainers as well as strategies to improve competencies in academic research activities and ultrasound training are recommendations to improve the Portuguese training curricula.Conclusion Addressing the gaps between expected and monitored competencies contributes to the advancement of anaesthesiology training. The survey drew attention to the ETR among the residents.Trial registration Not applicable – registered on OSF Registries.